PENDIDIKAN AKHLAK BERBASIS ALAM BAGI SISWA AUTISME MELALUI PENERAPAN PRINSIP PERILAKU TERAPAN - Haikal Firdaus, Ahmad; Khadijah, Siti; Miftahudin, Miftahudin; Iksan, Iksan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to explore the effectiveness of nature-based moral education in enhancing the understanding and practice of morals among autistic students through the application of Applied Behavior Analysis (ABA) principles. Moral education is crucial for autistic students to foster better social interactions and adaptive moral comprehension. This study employed a qualitative approach utilizing a case study method, involving participatory observation, in-depth interviews with educators and parents, and relevant document analysis. The research subjects were autistic students in an inclusive educational institution that had implemented a nature-based moral education program. Key findings indicate that the natural environment, rich in sensory and interactive stimuli, significantly facilitated the learning of moral concepts such as honesty, patience, and empathy. The application of ABA principles, including positive reinforcement and gradual behavior shaping, proved effective in guiding autistic students to internalize and express desired moral behaviors within natural contexts. The conclusion of this study affirms that nature-based moral education combined with ABA principles is a promising strategy for character development in autistic students, promoting their independence, and improving their quality of life